Business Ethics as a Field of Teaching, Training, and Research in Central Asia - Erdener, Carolyn (2011)
Central Asia presents a unique configuration of historical experience and societal responses that have been interacting and evolving for thousands of years. The current era of economic, political, and societal transformation in Central Asia began with the peaceful devolution of the Soviet Union and transition to the Commonwealth of Independent States in December 1991. Expectations about the natural social order based on western beliefs and experience may not apply in this part of the world, for—like all transitional and emerging market economies—Central Asia has inherited another social order that predates recent history. The field of Business Ethics provides an arena in which these issues can be explored. In this article, an overview of the current standing of Business Ethics as a field for teaching, training, and research in Central Asia is provided. Suggestions for further consideration and future research are presented in the concluding section.
Keywords: Research; Teaching; Training; Emerging markets; transitional economies; Business Ethics; Central Asia